Comparison between Balloon Inflation and Uterovaginal packing after Vaginal Delivery in Term of Control of Primary PPH - Sadaf Un Nisa, Shams Un Nisa, Mahnoor Athar, Nadia Zulfiqar, Bilqees Akhtar Malik, Nadia Leghari (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare balloon inflation with uterovaginal packing after vaginal delivery in term of control of primary post-partum hemorrhage. Study design: Randomized Controlled Trial. Study duration: May 2022 to November 2022 Setting: Department of Obstetrics & Gynecology Bahawal Victoria Hospital Bahawalpur. Methods: Total 140 patients of PPH after vaginal delivery age between 18-40 years, all parity and both booked and un-booked were selected and control of PPH was compared. Results: Total140 females who experienced PPH after vaginal delivery were enlisted in this study. Their mean age was 28.41 ± 5.894 years. In the Balloon inflation group and Uterovaginal packing group, the mean ages were 28.14 ± 6.240 years and 28.69 ± 5.557 years, respectively. Balloon inflation was utilized in the Balloon inflation group, and it was observed to be efficacious in controlling PPH in 39 (55.71%) patients. However, in the Uterovaginal packing group, uterovaginal packing was utilized and was noted to have controlled Primary PPH in 59 (84.29%) patients after vaginal delivery. The control rate of primary PPH was observed to be significantly (P=0.000) higher in the uterovaginal packing group when compared to the balloon inflation group. Practical implication: that for the control of PPH after vaginal delivery, uterovaginal packing is more effective in control of PPH than balloon inflation. Conclusion: Our study concluded that for the control of PPH after vaginal delivery, uterovaginal packing is more effective in control of PPH than balloon inflation. Keywords: Vaginal delivery, PPH,uterovaginal packing, balloon inflation